BUDAYA KERJA ISLAMI DI BRI SYARI’AH DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN - Endah Yuliani; Rifky Ardhana Kisno Saputra (J-MACC, 2020)
The purpose of this study is to see the influence of the Islamic Work Culture "PASTI OKE" on the employee performance of BRI Syari'ah Banyuwangi branch offices, using a quantitative descriptive approach. With the census determination method a sample of 28 employees. The technique of collecting data uses observation techniques, interview techniques, questionnaire techniques or documentation questionnaire techniques. Meanwhile, the instrument used in this study was a questionnaire or a questionnaire. The test instrument used was the validity and reliability test, the data transformation used the excel program. By using data analysis through multiple regression (multiole regression), the results of the study show that the Islamic Work Culture "PASTI OKE" has a positive effect on employee performance.